Moving reaction fronts in fractal nanoparticle agglomerates. (12th October 2019) - Jin, Wenjie; van Ommen, J. Ruud; Kleijn, Chris R.
Highlights: We investigate the saturation time of self-limiting reactions in nanoporous media. Our theory gives four time scales governing the reaction front penetration. Molecular simulations show excellent agreement with this theoretical model. Fractal dimension and agglomerate size determine the scaling of saturation time. Large fractal agglomerates saturate much faster than non-fractal agglomerates. Abstract: Self-limiting gas-surface reactions lead to reaction fronts that penetrate nanoporous materials with a finite speed. We present a closed form theoretical model, validated against molecular simulations, that shows the influence of the fractal scaling law on the time needed to fully penetrate fractal agglomerates of nanoparticles. For very large agglomerate sizes, this penetration time scales with the number of particles N in the agglomerate as N D f - 1 D f . The penetration time for agglomerates with fractal dimensions D f < 3 may therefore be orders of magnitude smaller than for non-fractal porous materials.